Validity and reliability of the Turkish version of the selfperceived food literacy scale: Self-Perceived Food Literacy Scale - Tarı Selçuk, Kevser; Çevik, Celalettin; Baydur, Hakan; Meseri, Reci (Progress in Nutrition, 2020)
Purpose: The present study was aimed at adapting the Self-Perceived Food Literacy Scale into Turkish and investigating its psychometric properties. Methods: This study was conducted with 391 adults aged ≥18 years living in a provincial center. This five-point likert scale consists of 29 items and 8 sub-scales. In the analysis of the study data, cronbach’s alpha values, ıntraclass correlation coefficient and item-total and inter-scale correlation coefficients were calculated, and the confirmatory factor analysis and linear regression analysis were performed. Results: The cronbach’s alpha value was 0.84, 0.70, 0.76, 0.61, 0.89, 0.69, 0.90, 0.92 for the subscales respectively (food preparation skills, resilience and resistance, healthy snack styles, social and conscious eating, examining food labels, daily food planning, healthy budgeting, healthy food stockpiling) and 0.83 for the overall scale. The test-retest intraclass correlation coefficient is between 0.80 and 0.96. The goodness of fit values of the confirmatory factor analysis are between 0.062-0.93. Conclusion: The Self- Perceived Food Literacy Scale adapted to Turkish society is a valid and reliable scale.